Career Adaptability, Work Engagement, and Employee Well-Being Among Chinese Employees: The Role of Guanxi - Yang, Xuhua; Feng, Yaqian; Meng, Yuchen; Qiu, Yong (Frontiers in Psychology, 2019)
The present study examined how career adaptability predicts employee well-being based on career construction theory. A three-wave questionnaire design was used to collect the data and 338 employees participated in the study. The results suggest that career adaptability has a significant effect on work engagement, which, in turn, predicts employee well-being. In addition to developing a mediation model, we also tested the effect of guanxi as a moderator. A moderated-mediation model was constructed in this research. The indirect effect of career adaptability on employee well-being through work engagement is stronger when guanxi is low than when it is high. This study provides a constructive replication of the findings on work engagement as a mediator in the relationship between career adaptability and employee well-being. Another novel aspect is the authors’ focus on differences in guanxi, which draws attention to the contextual factors that may shape the way employees respond to career adaptability. Furthermore, we discuss the limitations of this study and the implications for future research on career adaptability and employee well-being.